Toward Sustainable Practice: Exploring Career Pathways, Supports, and Challenges, Sustainability and Digital Transformation in Water Engineering Practice - (:unkn) unknown (My University, 2025)
In the face of accelerating climate change and global water scarcity, the necessity for resilient, equitable, and sustainable water infrastructure has become increasingly pressing. Water engineering plays a pivotal role in addressing this challenge, yet its effective management requires more than merely technical solutions. It necessitates a comprehensive evaluation of the support, development, and retention strategies employed within the water engineering sector. This research investigates the multifaceted dimensions of sustainable practice within water engineering by conducting in-depth interviews with professionals across the sector. Using a qualitative methodology, this study employed semi-structured interviews with water sector professionals, analyzed through thematic analysis to identify recurring patterns and narratives. The study identifies six interconnected themes that influence career development and organizational effectiveness: effective communication, supportive work environments, consultancy experiences with the water industry, digital transformation, internship experiences, and gender discrimination. The findings reveal that effective communication is a foundational skill that enhances collaboration, leadership, and stakeholder engagement, especially in an increasingly interdisciplinary and interconnected sector. Supportive work environments, defined by mentorship, open dialogue, and emotional safety, play a critical role in fostering resilience, professional growth, and long-term workforce retention. Early career experiences through internships and consultancy positions serve as vital touchpoints, helping individuals navigate complex technical projects, build confidence, and discover their professional identity. Digital transformation is reshaping the sector not only through new technologies such as automation and data-driven monitoring but also through shifts in organizational culture, remote work, and expectations for digital literacy. In this context, self-improvement and self-learning emerge as essential tools for career advancement, enabling professionals to remain agile and ready for the future. Simultaneously, the persistence of gender discrimination continues to erode psychological safety and inclusivity in the workplace, with women in particular facing systemic barriers to recognition and leadership. Ultimately, this study explores that sustainable practice in water engineering is not solely a matter of technical innovation, it requires an integrated approach that values interpersonal skills, continuous learning, inclusive leadership, and structural change. To meet the escalating demands of global water management and climate adaptation, the sector must invest in building work environments that are not only technically proficient but also socially conscious, digitally adaptive, and genuinely inclusive. This holistic perspective is essential to cultivating a workforce capable of driving sustainability, equity, and innovation in the 21st century.
Keywords: Civil engineering; Environmental engineering; Career Development; Global Water Scarcity; Qualitative Research; Water Industry